Microporous-mesoporous X molecular sieve as well as preparation and application thereof

By ion exchange and heat treatment on the NaX molecular sieve, microporous-mesoporous X molecular sieve is formed, which solves the problem of insufficient adsorption selectivity and mass transfer ability when separating paraxylene from mixed C8 aromatics in the prior art, and achieves high-efficiency and high-purity separation performance.

CN119911926APending Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311426611.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

When the prior art isolate paraxylene from mixed C8 aromatic hydrocarbons, the adsorption selectivity, adsorption capacity and mass transfer capacity are insufficient, making it difficult to meet the high purity and high efficiency requirements of industrial production.

Method used

Microporous-mesoporous X molecular sieve was used to ion exchange the NaX molecular sieve through barium salt and ammonium salt solution. Combined with heat treatment technology, a molecular sieve with a microporous specific surface area of ​​450-640m2/g and a mesoporous specific surface area of ​​20-50m2/g.

Benefits of technology

It significantly improves the adsorption selectivity and mass transfer capacity of aromatic hydrocarbons, improves the separation performance and adsorption capacity of paraxylene, and meets the efficient separation needs of industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004522400290000091
    Figure BDA0004522400290000091
  • Figure BDA0004522400290000092
    Figure BDA0004522400290000092
  • Figure BDA0004522400290000151
    Figure BDA0004522400290000151
Patent Text Reader

Abstract

The invention relates to a micropore-mesopore X molecular sieve, which is measured by a nitrogen physical adsorption method, the micropore specific surface area is 450-640m < 2 > / g, the mesopore specific surface area is 20-50m < 2 > / g, the pore size distribution curve shows at least two mesopore distribution peaks, the most probable pore size corresponding to one mesopore distribution peak is in the range of 3.0-7.0 nm, and the most probable pore size corresponding to the other mesopore distribution peak is in the range of 3.0-7.0 nm. And the most probable pore diameter corresponding to the other mesoporous distribution peak is in the range of 10.0-19.0 nm. The molecular sieve has good mass transfer performance and high aromatic hydrocarbon adsorption selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of molecular sieves, and in particular to a microporous-mesoporous X molecular sieve and its preparation and application. Background Art

[0002] Aromatic monomers are an important type of petrochemical basic raw material with high product added value. They can be widely used in the production of polyester, pesticides, medicines and other fields. In industrial production, adsorption separation technology is mostly used to separate aromatic monomers from aromatic mixtures. The most widely used scenario of this technology is the separation of paraxylene from mixed C8 aromatics. Through the simulated moving bed process, the mixed C8 aromatics and the adsorbent are repeatedly subjected to mass transfer exchange, so that paraxylene is enriched in the adsorbent, and then high-purity paraxylene is obtained through desorption and distillation operations.

[0003] At present, X molecular sieve is widely used as the active component of the adsorbent for separating p-xylene from mixed C8 aromatics. The three important indicators for evaluating its adsorption performance are adsorption selectivity, adsorption capacity and mass transfer capacity. The adsorption selectivity of X molecular sieve for C8 aromatic isomers is mainly affected by the properties of the molecular sieve and the type of exchange cations. At the same time, the improvement of the mass transfer performance of the adsorbent is also conducive to improving the performance of the adsorbent. Summary of the invention

[0004] The purpose of the present application is to provide a microporous-mesoporous X molecular sieve and its preparation and application, wherein the X molecular sieve has good mass transfer performance and high aromatics adsorption selectivity.

[0005] In order to achieve the above-mentioned object, on the one hand, the present application provides a microporous-mesoporous X molecular sieve, which has a micropore specific surface area of ​​450-640 m 2 / g, mesopore specific surface area is 20-50m 2 / g, and its pore size distribution curve shows at least two mesopore distribution peaks, wherein the most probable pore size corresponding to one mesopore distribution peak is in the range of 3.0-7.0nm, and the most probable pore size corresponding to the other mesopore distribution peak is in the range of 10.0-19.0nm.

[0006] Preferably, the mesopore volume ratio corresponding to the two mesopore distribution peaks is (100-20): (10-5) from small to large pore size.

[0007] On the other hand, a method for preparing the microporous-mesoporous X molecular sieve of the present application is provided, comprising the following steps:

[0008] 1) Partially ion exchange the NaX molecular sieve with a barium salt solution to obtain a Ba-modified molecular sieve;

[0009] 2) performing partial ion exchange on the Ba-modified molecular sieve obtained in step 1) with an ammonium salt solution to obtain an ammonium-exchanged molecular sieve; and

[0010] 3) The ammonium-exchanged molecular sieve obtained in step 2) is heat-treated at 100-500° C. for 0.5-6.0 h under a flowing atmosphere, and optionally, the heat-treated molecular sieve is ion-exchanged with a mixed solution of barium salt and potassium salt, or with a barium salt solution and a potassium salt solution respectively, to obtain a microporous-mesoporous X molecular sieve.

[0011] In another aspect, the present invention provides the use of the microporous-mesoporous molecular sieve as an adsorbent, in particular, the use of the microporous-mesoporous molecular sieve as an adsorbent for the adsorptive separation of aromatic isomers.

[0012] The microporous-mesoporous X molecular sieve of the present application has a large micropore specific surface area and at least two mesoporous channels with different pore sizes. When used for the adsorption separation of aromatic isomers, it shows improved mass transfer capacity and significantly improved separation performance.

[0013] Other features and advantages of the present application will be described in detail in the subsequent specific implementation section. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] The accompanying drawings are used to provide a further understanding of the present application and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present application but do not constitute a limitation to the present application. In the accompanying drawings:

[0015] Figure 1 The XRD spectrum of the X molecular sieve prepared in Example 1 of the present application;

[0016] Figure 2 The pore size distribution curve of the X molecular sieve prepared in Example 1 of the present application;

[0017] Figure 3 The X molecular sieve prepared in Example 1 of this application 29 Si solid NMR spectrum curve;

[0018] Figure 4 The X molecular sieve prepared in Example 1 of this application 27 Al solid NMR spectrum curve;

[0019] Figure 5 The pore size distribution curve of the X molecular sieve prepared in Example 2 of the present application;

[0020] Figure 6 The X molecular sieve prepared in Example 2 of this application 29 Si solid NMR spectrum curve;

[0021] Figure 7 The X molecular sieve prepared in Example 2 of this application27 Al solid NMR spectrum curve;

[0022] Figure 8 The pore size distribution curve of the X molecular sieve prepared in Comparative Example 1 of the present application;

[0023] Fig. 9 The pore size distribution curve of the X molecular sieve prepared in Comparative Example 2 of the present application; and

[0024] Fig.10 This is the pore size distribution curve of the X molecular sieve prepared in Comparative Example 3 of the present application. DETAILED DESCRIPTION

[0025] The specific implementation methods of the present application are described in detail below, but it should be noted that the protection scope of the present application is not limited by these specific implementation methods, but is determined by the claims in the appendix.

[0026] Any specific numerical value disclosed herein (including the endpoint of the numerical range) is not limited to the exact value of the numerical value, but should be understood to also cover values ​​close to the exact value, such as all possible numerical values ​​within the range of ±5% of the exact value. In addition, for the disclosed numerical range, the endpoint values ​​of the range, the endpoint values ​​and the specific point values ​​in the range, and the specific point values ​​can be arbitrarily combined to obtain one or more new numerical ranges, and these new numerical ranges should also be regarded as specifically disclosed herein.

[0027] Unless otherwise specified, the terms used herein have the same meaning as commonly understood by those skilled in the art. If a term is defined herein and its definition is different from the commonly understood meaning in the art, the definition herein shall prevail.

[0028] In the present application, the micropore and mesopore pore volumes, specific surface areas and pore size distributions of molecular sieves are determined by nitrogen physical adsorption method.

[0029] In this application, except for the contents clearly stated, any matters or items not mentioned are directly applicable to the aspects known in the art without any changes. Moreover, any embodiment described herein can be freely combined with one or more other embodiments described herein, and the technical solutions or technical ideas formed thereby are deemed to be part of the original disclosure or original record of this application, and should not be regarded as new contents not disclosed or anticipated herein, unless a person skilled in the art considers that the combination is obviously unreasonable.

[0030] All patent and non-patent literature, including but not limited to textbooks and journal articles, mentioned herein are incorporated herein by reference in their entirety.

[0031] Without being limited to a specific theory, the inventors of the present application have found through extensive research that the use of ammonium salt solution to treat Na-Ba-X molecular sieves can make NH4 + Ions and some Na + and Ba 2+ Ions are exchanged, and in the subsequent heat treatment process, NH4 + It will be converted into gaseous ammonia and hydrogen protons. Due to the unstable framework structure of the H-type molecular sieve with a low silicon-aluminum ratio, part of the framework is destroyed to produce mesopores. 2+ Limited by steric hindrance, it is difficult to occupy the type III exchange site on the four-membered ring of the FAU molecular sieve β cage. + and Ba 2+ The difference in the distribution of ions in the molecular sieve framework leads to the breaking of Si-O-Al bonds at different positions after ammonium exchange and heat treatment, thus forming mesopores with different pore sizes. The presence of such mesopores significantly improves the intracrystalline mass transfer capacity of the molecular sieve. + The exchange concentration of ions and the temperature of heat treatment allow the mesoporous channels to be constructed while retaining the microporous channels of the molecular sieve to the maximum extent, thereby ensuring the adsorption capacity of the molecular sieve and the separation performance of p-xylene, thereby obtaining the present invention.

[0032] As described above, in the first aspect, the present application provides a microporous-mesoporous X molecular sieve, the micropore specific surface area of ​​which is 450-640 m 2 / g, mesopore specific surface area is 20-50m 2 / g, and its pore size distribution curve shows at least two mesopore distribution peaks, wherein the most probable pore size corresponding to one mesopore distribution peak is in the range of 3.0-7.0nm, and the most probable pore size corresponding to the other mesopore distribution peak is in the range of 10.0-19.0nm.

[0033] In a preferred embodiment, the micropore specific surface area of ​​the microporous-mesoporous X molecular sieve is 500-640 m 2 / g, preferably 550-640m 2 / g, mesopore specific surface area is 20-30m 2 / g, and its pore size distribution curve shows at least two mesopore distribution peaks, wherein the most probable pore size corresponding to one mesopore distribution peak is in the range of 4.5-7.0nm, and the most probable pore size corresponding to the other mesopore distribution peak is in the range of 10.0-14.0nm.

[0034] In a preferred embodiment, the mesopore volume ratio corresponding to the two mesopore distribution peaks is (100-20):(10-5) from small to large pore size, preferably (80-60):(10-8).

[0035] In a preferred embodiment, the pore size distribution curve of the X molecular sieve shows at least three mesopore distribution peaks, wherein the most probable pore size corresponding to one mesopore distribution peak is in the range of 3.0-7.0 nm, the most probable pore size corresponding to one mesopore distribution peak is in the range of 10.0-19.0 nm, and the most probable pore size corresponding to another mesopore distribution peak is in the range of 19.0-30.0 nm.

[0036] In a further preferred embodiment, the pore size distribution curve of the X molecular sieve shows at least three mesopore distribution peaks, wherein the most probable pore size corresponding to one mesopore distribution peak is in the range of 4.5-7.0 nm, the most probable pore size corresponding to one mesopore distribution peak is in the range of 10.0-14.0 nm, and the most probable pore size corresponding to another mesopore distribution peak is in the range of 19.0-26.0 nm.

[0037] In a further preferred embodiment, the mesopore volume ratios corresponding to the three mesopore distribution peaks are (100-20): (10-5): (1-0.1) from small to large pore size, preferably (80-60): (10-8): (1-0.5).

[0038] The microporous-mesoporous X molecular sieve of the present application has a high micropore specific surface area, so that it has a high adsorption capacity, and at the same time has mesoporous channels with a variety of different pore sizes, which improves the mass transfer of the adsorbate in the molecular sieve crystal. When it is used for the adsorption separation of aromatic isomers (such as C8 mixed aromatics), it shows improved mass transfer capacity and significantly improved separation performance.

[0039] In a preferred embodiment, the SiO2 / Al2O3 molar ratio of the X molecular sieve is 2.0-2.6, such as 2.0, 2.1, 2.2, 2.3, 2.4, 2.5 or 2.6, preferably 2.2-2.4.

[0040] In a preferred embodiment, the total pore volume of the X molecular sieve is 0.24-0.35 cm 3 ·g -1 The micropore volume is in the range of 0.22-0.33cm 3 ·g -1 Further preferably, the total pore volume of the X molecular sieve is in the range of 0.26-0.35 cm 3 ·g -1 The micropore volume is in the range of 0.24-0.33cm 3 ·g -1More preferably, the percentage of micropore volume of the X molecular sieve to total pore volume is not less than 90.0%, for example, 90.0-99.0%, such as 90.0%, 91.0%, 92.0%, 93.0%, 94.0%, 95.0%, 96.0%, 97.0%, 98.0% or 99.0%, etc.

[0041] In a preferred embodiment, the particle size of the X molecular sieve is 0.8-2.5 μm, such as 0.8 μm, 1.0 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2.0 μm, 2.2 μm or 2.4 μm, preferably 0.8-1.5 μm.

[0042] In a preferred embodiment, by 29 Si and 27 According to Al high-resolution magic angle nuclear magnetic resonance measurement, the relative content of the sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in the framework structure of the X molecular sieve is not less than 60 mol%, for example, 60-95 mol%, such as 60 mol%, 70 mol%, 80 mol%, 90 mol% or 95 mol%, and the relative content of non-framework aluminum in the total aluminum species is not higher than 3 mol%, for example, 0-3 mol%, such as 0.2 mol%, 0.5 mol%, 0.6 mol%, 0.8 mol%, 1.0 mol%, 1.5 mol%, 2.0 mol%, 2.5 mol% or 3.0 mol%. Further preferably, the relative content of the sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in the framework structure of the X molecular sieve is not less than 75 mol%, particularly preferably not less than 80 mol%, for example 80-95 mol%, and the relative content of non-framework aluminum in the total aluminum species is not higher than 1.6 mol%, particularly preferably not higher than 0.8 mol%, for example 0-0.8 mol%.

[0043] In certain preferred embodiments, at least part of the cation positions of the X molecular sieve are occupied by Ba and Na. The Ba mass content of the X molecular sieve is in the range of 5.0-41.0% calculated as BaO, for example, 5.0%, 10.0%, 15.0%, 20.0%, 25.0%, 30.0%, 35.0%, 40.0% or 41.0%; the Na mass content of the X molecular sieve is in the range of 0.2-17.0% calculated as Na2O, for example, 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2.%, 1.4%, 1.6%, 1.8%, 2.0%, 4.0%, 6.0%, 8.0%, 10.0%, 12.0%, 14.0%, 16.0% or 17.0%. Further preferably, the Ba mass content of the X molecular sieve is in the range of 30-41.0% calculated as BaO; and the Na mass content of the X molecular sieve is in the range of 0.2-2.0% calculated as Na2O.

[0044] In other preferred embodiments, at least part of the cation positions of the X molecular sieve are occupied by Ba and K. The Ba mass content of the X molecular sieve is in the range of 30.0-41.0% calculated as BaO, for example, 30.0%, 32.5%, 35.0%, 37.5%, 40.0%, 40.5% or 41.0%; the K mass content of the X molecular sieve is in the range of 0.2-3.0% calculated as KO, for example, 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2.%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8% or 3.0%. Further preferably, the Ba mass content of the X molecular sieve is in the range of 38.0-41.0% calculated as BaO; and the K mass content of the X molecular sieve is in the range of 0.2-2.0% calculated as K2O.

[0045] In a second aspect, a method for preparing the microporous-mesoporous X molecular sieve of the present application is provided, comprising the following steps:

[0046] 1) Partially ion exchange the NaX molecular sieve with a barium salt solution to obtain a Ba-modified molecular sieve;

[0047] 2) performing partial ion exchange on the Ba-modified molecular sieve obtained in step 1) with an ammonium salt solution to obtain an ammonium-exchanged molecular sieve; and

[0048] 3) The ammonium-exchanged molecular sieve obtained in step 2) is heat-treated at 100-500° C. for 0.5-6.0 h under a flowing atmosphere, and ion exchange is optionally performed using a mixed solution of barium salt and potassium salt, or using the molecular sieve heat-treated with a barium salt solution and a potassium salt solution respectively, to obtain a microporous-mesoporous X molecular sieve.

[0049] In a preferred embodiment, the NaX molecular sieve used in step 1) has one or more of the following characteristics: an octahedral morphology, a particle size of 0.8-2.5 μm, preferably 0.8-1.5 μm, a SiO2 / Al2O3 molar ratio of 2.0-2.6, preferably 2.2-2.4, and a Na mass fraction of 15.0-17.0% based on Na2O.

[0050] According to the present application, in step 1), the NaX molecular sieve is partially ion exchanged with a barium salt solution, so that part of the Na on the cation position of the molecular sieve is + Ions are Ba 2+ ions are replaced, thereby obtaining a Ba-modified molecular sieve. In a preferred embodiment, the partial ion exchange of step 1) is carried out at a temperature of 30-95°C, such as 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, or 95°C for 0.5-5.0h, such as 0.5h, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h or 5.0h. Further preferably, the partial ion exchange of step 1) is carried out at 80-95°C for 2.0-5.0h. Under the above conditions, the Ba-modified molecular sieve obtained has a Ba content in the range of 5.0-35.0% calculated as BaO, preferably in the range of 25.0-35.0%; and a Na content in the range of 1.0-10.0% by mass calculated as Na2O, preferably in the range of 1.0-5.0%. In step 1), too high an ion exchange temperature will cause the molecular sieve framework structure to be destroyed, and too low a temperature and too short a time will cause Ba 2+ Insufficient exchange volume and too long a time will lead to Ba 2+ The complete exchange of the two is not conducive to the subsequent formation of mesoporous channels with various pore sizes.

[0051] In a further preferred embodiment, in step 1):

[0052] The concentration of the barium salt solution is 0.05-1.0 mol / L, for example, 0.05 mol / L, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L or 1.0 mol / L;

[0053] The barium salt is selected from barium chloride, barium nitrate, or a combination thereof; and / or

[0054] When the barium salt solution is subjected to ion exchange with the NaX molecular sieve, the volume space velocity of the barium salt solution is 2.0-10.0 h -1 , for example 2h -1 , 3h -1 , 4h -1 , 5h -1 , 6h -1 , 7h -1 , 8h -1 , 9h -1 or 10h -1 .

[0055] Optionally, before step 2), the Ba-modified molecular sieve obtained in step 1) may be dried, and the drying conditions include: temperature 50-120°C, for example 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, and time not less than 2.0 h, for example 2.0-12.0 h.

[0056] According to the present application, in step 2), the Ba-modified molecular sieve obtained in step 1) is partially ion-exchanged with an ammonium salt solution, so that part of the Na on the cation position of the molecular sieve is + ions and / or Ba 2+ Ions are NH4 + ions are replaced, thereby obtaining an ammonium exchanged molecular sieve. In a preferred embodiment, the partial ion exchange of step 2) is carried out at a temperature of 25-95°C, such as 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 95°C for 0.2-5.0h, such as 0.2h, 0.5h, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h or 5.0h. Further preferably, the partial ion exchange of step 2) is carried out at 50-75°C for 0.2-2.0h. Under the above conditions, the obtained ammonium exchanged molecular sieve has a Ba content in the range of 3.0-33.0% calculated as BaO, preferably in the range of 22.0-33.0%; and a Na content in the range of 0.2-8.0% by mass calculated as Na2O, preferably in the range of 0.2-5.0%. In step 2), too high an ion exchange temperature will cause the molecular sieve framework structure to be destroyed, and too low a temperature and too short a time will cause NH4 + Insufficient exchange capacity will result in failure to form mesopores during subsequent heat treatment, and too long a treatment time will result in NH4 + Excessive exchange will cause damage or even complete collapse of the molecular sieve framework structure during the subsequent heat treatment.

[0057] In a preferred embodiment, in step 2):

[0058] The concentration of the ammonium salt solution is 0.2-5.0 mol / L, for example, 0.2 mol / L, 0.5 mol / L, 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, 2.5 mol / L, 3.0 mol / L, 3.5 mol / L, 4.0 mol / L, 4.5 mol / L or 5.0 mol / L;

[0059] The ammonium salt is selected from ammonium chloride, ammonium sulfate, ammonium nitrate, or a combination thereof; and / or

[0060] When the ammonium salt solution and the Ba-modified molecular sieve are subjected to ion exchange, the liquid-to-solid volume ratio of the ammonium salt solution to the molecular sieve is 0.1-10:1, for example, 0.1:1, 0.5:1, 1:1, 1.5:1, 2.0:1, 2.5:1, 3.0:1, 3.5:1, 4.0:1, 4.5:1, 5.0:1, 5.5:1, 6.0:1, 6.5:1, 7.0:1, 7.5:1, 8.0:1, 8.5:1, 9.0:1, 9.5:1 or 10:1, preferably 1-5:1.

[0061] According to the present application, in step 3), the ammonium exchanged molecular sieve is heat treated so that the NH4 + Converted into gaseous ammonia and hydrogen protons. In this process, due to the unstable framework structure of the H-type molecular sieve with low silicon-aluminum ratio and Na + and Ba 2+ The difference in the distribution position of ions in the molecular sieve framework leads to the formation of mesopores with a variety of different pore sizes. According to the present application, the heat treatment of step 3) is carried out at a temperature of 100-500°C under a flowing atmosphere, for example, at 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C or 500°C, for 0.5-6.0h, for example, 0.5h, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h or 6.0h. In a preferred embodiment, the heat treatment of step 3) is carried out at 120-300°C for 2.0-6.0h under a flowing atmosphere. In step 3), too high a heat treatment temperature and too long a heat treatment time will cause the molecular sieve framework structure to be destroyed, resulting in a loss of adsorption capacity, while too low a treatment temperature and too short a treatment time will not be sufficient to form mesoporous channels.

[0062] In a preferred embodiment, in step 3), the gas flow rate of the flowing atmosphere is 0.01-1.0 L / h / g molecular sieve, for example, 0.01 L / h / g, 0.03 L / h / g, 0.05 L / h / g, 0.08 L / h / g, 0.1 L / h / g, 0.2 L / h / g, 0.3 L / h / g, 0.4 L / h / g, 0.5 L / h / g, 0.6 L / h / g, 0.7 L / h / g, 0.8 L / h / g, 0.9 L / h / g or 1.0 L / h / g molecular sieve.

[0063] According to the present application, the flowing atmosphere in step 3) can be a flowing air atmosphere or an inert flowing atmosphere, such as a flowing nitrogen atmosphere, preferably a flowing air atmosphere.

[0064] In certain specific embodiments, the method for preparing the microporous-mesoporous X molecular sieve of the present application comprises the following steps:

[0065] 1) adding NaX molecular sieve into barium salt solution, soaking at 80-95° C. for 2.0-5.0 h, filtering and washing to obtain Ba-modified molecular sieve;

[0066] 2) adding the Ba-modified molecular sieve obtained in step 1) into an ammonium salt solution, soaking it at 50-75° C. for 0.2-2.0 h, and filtering and washing it to obtain an ammonium-exchanged molecular sieve;

[0067] 3) heat treating the ammonium exchanged molecular sieve obtained in step 2) at 120-300° C. for 2.0-6.0 h under flowing air atmosphere to obtain a heat-treated molecular sieve; and

[0068] 4) adding the heat-treated molecular sieve obtained in step 3) into a mixed solution of barium salt and potassium salt, and soaking the mixture at 80-95° C. for 8.0-24.0 h to obtain a microporous-mesoporous X molecular sieve.

[0069] In a third aspect, there is provided the use of the microporous-mesoporous molecular sieve of the present application as an adsorbent, in particular, as an adsorbent for the adsorptive separation of aromatic isomers.

[0070] In certain preferred embodiments, the aromatic isomers are C8 mixed aromatics, in particular C8 mixed aromatics comprising p-xylene and at least one of its isomers, such as m-xylene, ethylbenzene, and the like.

[0071] In a fourth aspect, the present application provides a method for adsorbing and separating paraxylene from C8 mixed aromatics containing paraxylene by liquid phase adsorption separation, comprising the steps of contacting the C8 mixed aromatics with the microporous-mesoporous molecular sieve of the present application to adsorb paraxylene, and contacting the molecular sieve after adsorbing paraxylene with a desorbent to desorb the paraxylene.

[0072] In a preferred embodiment, the liquid phase adsorption separation can be carried out by connecting multiple columns in series, or by using a simulated moving bed realized by a rotary valve or a solenoid valve group.

[0073] In a preferred embodiment, the desorbent is selected from p-diethylbenzene, toluene, or a combination thereof.

[0074] In a preferred embodiment, the operating pressure of the adsorption separation is 0.3-1.5 MPa, for example, 0.3 MPa, 0.5 MPa, 0.8 MPa, 1.0 MPa, 1.2 MPa, 1.4 MPa or 1.5 MPa, and the operating temperature is 120-180°C, for example, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C.

[0075] Example

[0076] In the following examples and comparative examples:

[0077] The total pore volume, micropore volume, mesopore volume, specific surface area and pore size distribution of the molecular sieve were determined by nitrogen physical adsorption method. The test instrument was ASAP 2020 physical adsorption instrument from Micromeritics, USA. Before the test, the samples were heated at 300-450℃ and vacuum (<10 -2 The degassing was carried out at 77K for 6.0-16.0h, preferably at 300°C for 10.0h. Nitrogen physical adsorption was carried out at 77K. The total specific surface area and average adsorption pore size of the molecular sieve were calculated by the BET (Brunauer-Emmett-Teller) equation; P0 was 0.1Mpa, and the total pore volume of the sample was determined by the adsorption amount of nitrogen when the relative adsorption amount P / P0=0.975 was used, and the micropore surface area, external specific surface area and micropore volume were calculated using the t-plot method, and the pore size distribution of the mesopores was calculated using the BJH method (Barrett-Joyner-Halenda).

[0078] The elemental chemical composition of the molecular sieve is characterized by X-ray fluorescence spectrometry (XRF), and the instrument used is Shimadzu XRF-1800 X-ray fluorescence spectrometer. The qualitative analysis of BaO, K2O, Na2O, Al2O3 and SiO2 is carried out according to the corresponding relationship between the wavelength of characteristic X-ray fluorescence and the atomic number. The quantitative analysis of BaO, K2O, Na2O, Al2O3 and SiO2 can be carried out according to the comparison of the peak intensity at the wavelength of X-ray fluorescence and the standard sample. The SiO2 / Al2O3 molar ratio of the molecular sieve is calculated by the relative mass of SiO2 and Al2O3.

[0079] The crystal structure of the molecular sieve was determined using X-ray diffraction (XRD) on a PANalytical-XPert diffractometer from the Netherlands. The sample was ground to less than 200 mesh and then spread on a special glass carrier for testing. The radiation source was Cu Kα (λ = 0.154nm), the operating voltage was 40kV, the operating current was 40mA, the scanning range was 5°-35°, and the scanning rate was 4° / min.

[0080] Coordination number and existence form of silicon and aluminum atoms in molecular sieves 29 Si and 27 Al high resolution magic angle nuclear magnetic resonance (MAS NMR) characterization, 29 Si core and 27 The single pulse spectra of Al nuclei were completed using a Bruker Avance III 500WB spectrometer. 29 Si core and 27 The resonant frequencies of the Al core are 500.1MHz and 89.6MHz respectively. The relative content of the sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in the molecular sieve framework structure to the total silicon species is 29 The ratio of the sum of the peak areas corresponding to the chemical shifts -86 and -90 ppm in the Si MAS NMR spectrum to the sum of all the peak areas corresponding to the chemical shifts -70 to -120 ppm; the relative content of non-framework aluminum to total aluminum species is 27 The ratio of the peak area corresponding to 0 ppm in the Al MAS NMR spectrum to the sum of all peak areas corresponding to -20 to 100 ppm.

[0081] The information of the molecular sieve grain size is characterized by FE-SEM photos. The instrument used is a Japanese Hitachi S-4800 scanning electron microscope. The grain size within the range of 10.0 μm×10.0 μm is selected for measurement and calculation. The measured grain size is the average value of all grain sizes.

[0082] The adsorption capacity of the adsorbent material is determined by contacting nitrogen gas carrying toluene (toluene partial pressure is 0.5 MPa) with a certain mass of the adsorbent material at 35°C until toluene reaches adsorption equilibrium. The adsorption capacity of the adsorbent material is calculated based on the mass difference of the adsorbent material before and after toluene adsorption.

[0083] The mass transfer performance of the sample was determined by the zero-length column method: the sample was loaded into the column, the carrier gas was nitrogen, and the flow rate was 10 mL / min. After the sample was pretreated at 200 °C for 1 h, nitrogen containing p-xylene was passed through the zero-length column. When the detector signal remained stable, p-xylene was saturated with adsorption in the sample. At this time, the p-xylene concentration in the carrier gas was c0. Subsequently, the gas flowing through the zero-length column was switched to nitrogen, and the p-xylene concentration change curve in the carrier gas was recorded. The diffusion coefficient calculation formula is shown in equations (1) and (2):

[0084]

[0085]

[0086] Where: c0 is the molar concentration of p-xylene at adsorption saturation, mol / L; t is the contact time between nitrogen and sample, min; c t is the molar concentration of p-xylene at time t, mol / L; b is the intercept of the diffusion curve; k is the slope of the diffusion curve, min-1; D is the diffusion coefficient, μm 2 / min; d is the catalyst particle size, μm.

[0087] For ln(c t / c0)-t graph, the slope k of the fitted line can be obtained according to formula (1), and then the diffusion coefficient D of p-xylene in the molecular sieve pores is calculated according to formula (2). The diffusion coefficient of p-xylene in the NaX molecular sieve reference sample (SiO2 / Al2O3 molar ratio of 2.43, particle size of 1.0 μm, Na mass fraction of 16.7% in terms of Na2O) is used as a benchmark, and its relative diffusion coefficient is set to 1.00, so as to calculate the relative diffusion coefficient of the probe molecule in the X molecular sieve.

[0088] The adsorption selectivity and mass transfer performance of the adsorbent material were determined using a dynamic pulse test device: the device consists of a feed system, an adsorption column, a heating furnace, a pressure control valve, etc. The adsorption column is a Ф6×1800mm stainless steel tube, and the adsorption material loading is 50 ml. The lower inlet of the adsorption column is connected to the feed and nitrogen system, and the upper outlet is connected to the pressure control valve, and then connected to the effluent collector. The desorbent used in the experiment is 30 volume % of p-diethylbenzene (PDEB) and 70 volume % of n-heptane. The pulse feed liquid composition is 5 volume % of ethylbenzene (EB), p-xylene (PX), m-xylene (MX), o-xylene (OX), n-nonane (NC9) and 75 volume % of p-diethylbenzene.

[0089] The method for determining the adsorption selectivity of the adsorbent material is as follows: weigh the adsorbent material particles with a particle size of 300-850μm and place them into the adsorption column for compaction, dehydrate and activate them at 160-190℃ in a nitrogen atmosphere, and then introduce a desorbent to remove the gas in the system. Raise the system pressure to 0.8MPa and the temperature to 177℃, stop introducing the desorbent, and wait for 1.0h. -1 8 ml of pulse feed liquid was introduced at a volumetric space velocity, and then the desorbent was introduced at the same volumetric space velocity. Three drops of desorbent sample were taken every 2 minutes and analyzed by gas chromatography. The desorption curves of the above components were plotted with the volume of desorbent used for desorption as the horizontal coordinate and the concentrations of NC9, EB, PX, MX and OX as the vertical coordinate. Among them, NC9 is not adsorbed and can be used as a tracer to obtain the dead volume of the adsorption system. The midpoint of the half-peak width of the tracer is taken as the zero point, and the net retention volume R from the midpoint of the half-peak width of the components EB, PX, MX, and OX to the zero point is measured. The net retention volume of any component is proportional to the distribution coefficient at adsorption equilibrium, which reflects the interaction between each component and the adsorbent material. The ratio of the net retention volumes of the two components is the selectivity β. For example, the ratio of the net retention volume of PX to the net retention volume of EB is the ratio of the adsorption performance of the adsorbent for PX and EB, that is, the adsorption selectivity of the adsorbent for PX relative to EB, recorded as β P / E Similarly, the adsorption selectivity of the adsorbent material for PX relative to MX and OX is denoted as β P / M and β P / O The volume of desorbent required when the MX concentration in the effluent increases from 10% to 90% at the front edge of the pulse desorption curve of MX is defined as the adsorption rate [S A ] 10-90 The desorption rate [S D ] 90-10 ,[S A ] 10-90 With [S D ] 90-10 The smaller the value, the higher the mass transfer performance of the adsorption material.

[0090] In the following examples and comparative examples, unless otherwise specified, all reagents and raw materials used are commercially available products.

[0091] Example 1

[0092] Molecular sieve preparation

[0093] 100 g of NaX molecular sieve (SiO2 / Al2O3 molar ratio of 2.43, particle size of 1.0 μm, Na mass fraction of 16.7% in terms of Na2O) was ion exchanged with 0.18 mol / L barium chloride solution. The ion exchange was carried out in a column container at a temperature of 90°C for 3.0 h. The volumetric space velocity of the barium salt solution was 3.0 h. -1 , and then filtered and washed with 500 mL of deionized water, and dried at 90°C for 12.0 h to obtain Ba-modified molecular sieve X-1.

[0094] The obtained molecular sieve X-1 was added into 300 mL of 0.2 mol / L ammonium chloride solution for ion exchange at 50°C for 2.0 h. The product was filtered and washed with 500 mL of deionized water to obtain ammonium-exchanged molecular sieve X-2.

[0095] The obtained ammonium-exchanged molecular sieve X-2 was placed in a flowing air atmosphere with an air flow rate of 1 L / h / g molecular sieve for heat treatment at a heat treatment temperature of 200°C and a heat treatment time of 2.0 h to obtain a heat-treated molecular sieve X-3, whose Ba mass content was 32.5% as BaO and Na mass content was 1.7% as Na2O.

[0096] The heat-treated molecular sieve X-3 was ion exchanged with a mixed solution of 0.18 mol / L barium chloride and 0.07 mol / L potassium chloride. The ion exchange was carried out in a column container at a temperature of 90 °C for 8.0 h. The volumetric space velocity of the mixed solution was 6.0 h. -1 , and then the product was filtered and washed with 2000 mL of deionized water, and dried at 90° C. for 12.0 h to obtain a microporous-mesoporous X molecular sieve, wherein the Ba mass content of the obtained molecular sieve was 39.80% as BaO, and the K mass content was 0.60% as K2O.

[0097] The X-ray powder diffraction spectrum of the obtained X molecular sieve is shown in Figure 1 , pore size distribution curve see Figure 2 , solid-state NMR 29 Si spectrum is shown in Figure 3 , solid-state NMR 27 Al spectrum is shown in Figure 4 The SiO2 / Al2O3 molar ratio is 2.43, the grain size is 1.0 μm, the total pore volume measured by nitrogen physical adsorption is 0.325 mL / g, the micropore volume is 0.293 mL / g, and the micropore specific surface area is 636.1 m 2 / g, and the mesopore specific surface area is 22.7m 2 / g, the mesopore volume is 0.032mL / g, the most probable pore sizes corresponding to the three mesopore distribution peaks on the pore size distribution curve are 4.8nm, 12.8nm and 26.0nm respectively, the mesopore volume ratio corresponding to the three mesopore distribution peaks is 78:8:1, and the relative content of the sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in its framework structure accounts for 82mol% of the total silicon species, and the relative content of non-framework aluminum accounts for 0.6mol% of the total aluminum species.

[0098] Molecular sieve performance test

[0099] The obtained X molecular sieve sample was pressed into tablets under a pressure of 25 MPa, and after crushing and sieving, particles of 300-850 μm were obtained. The adsorption and separation performance of the molecular sieve sample for C8 aromatics was measured, and the results are shown in Table 1. The mass transfer capacity and adsorption capacity of the molecular sieve sample were measured, and the results are shown in Table 2.

[0100] Example 2

[0101] The X molecular sieve was prepared by referring to the method of Example 1, except that the concentration of the barium chloride solution used was 1.0 mol / L, and the concentration of the ammonium chloride solution was 3.0 mol / L. The Ba mass content of the obtained X molecular sieve was 38.57% calculated as BaO, and the K mass content was 0.56% calculated as K2O.

[0102] The pore size distribution curve of the obtained X molecular sieve is shown in Figure 5 , solid-state NMR 29 Si spectrum is shown in Figure 6 , solid-state NMR 27 Al spectrum is shown in Figure 7 The SiO2 / Al2O3 molar ratio is 2.43, the grain size is 1.0 μm, the total pore volume is 0.292 mL / g, the micropore volume is 0.260 mL / g, and the micropore specific surface area is 529.3 m 2 / g, and the mesopore specific surface area is 49.3m 2 / g, the mesopore volume is 0.032mL / g, the most probable pore sizes corresponding to the three mesopore distribution peaks on the pore size distribution curve are 6.4nm, 11.9nm and 20.3nm respectively, the mesopore volume ratio corresponding to the three mesopore distribution peaks is 69:9:0.7, the relative content of the sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in its framework structure accounts for 78mol% of the total silicon species, and the relative content of non-framework aluminum accounts for 1.5mol% of the total aluminum species.

[0103] The molecular sieve performance test was carried out with reference to Example 1. The test results are shown in Tables 1 and 2.

[0104] Example 3

[0105] The X molecular sieve was prepared by referring to the method of Example 1, except that the barium salt used was barium nitrate and the ammonium salt used was ammonium sulfate. The Ba mass content of the obtained X molecular sieve was 39.91% as BaO and the K mass content was 0.59% as K2O.

[0106] The obtained X molecular sieve has a SiO2 / Al2O3 molar ratio of 2.43, a grain size of 1.0 μm, a total pore volume of 0.319 mL / g, a micropore volume of 0.274 mL / g, and a micropore specific surface area of ​​595.5 m 2 / g, and the mesopore specific surface area is 43.6m 2 / g, the mesopore volume is 0.045mL / g, the most probable pore sizes corresponding to the three mesopore distribution peaks on the pore size distribution curve are 6.2nm, 11.8nm and 19.5nm respectively, the mesopore volume ratio corresponding to the three mesopore distribution peaks is 74:10:0.7, the relative content of the sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in its framework structure accounts for 79mol% of the total silicon species, and the relative content of non-framework aluminum accounts for 1.6mol% of the total aluminum species.

[0107] The molecular sieve performance test was carried out with reference to Example 1. The test results are shown in Tables 1 and 2.

[0108] Example 4

[0109] The X molecular sieve was prepared by referring to the method of Example 1, except that the temperature of the barium chloride solution treatment was 50° C., and the temperature of the ammonium chloride solution treatment was 85° C. The Ba mass content of the obtained X molecular sieve was 40.30% as BaO, and the K mass content was 0.59% as K2O.

[0110] The obtained X molecular sieve has a SiO2 / Al2O3 molar ratio of 2.43, a grain size of 1.0 μm, a total pore volume of 0.296 mL / g, a micropore volume of 0.258 mL / g, and a micropore specific surface area of ​​561.0 m 2 / g, and the mesopore specific surface area is 32.7m 2 / g, the mesopore volume is 0.038mL / g, the most probable pore sizes corresponding to the three mesopore distribution peaks on the pore size distribution curve are 5.4nm, 12.1nm and 20.4nm respectively, the mesopore volume ratio corresponding to the three mesopore distribution peaks is 77:6:0.9, and the relative content of the sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in its framework structure accounts for 83mol% of the total silicon species, and the relative content of non-framework aluminum accounts for 0.6mol% of the total aluminum species.

[0111] The molecular sieve performance test was carried out with reference to Example 1. The test results are shown in Tables 1 and 2.

[0112] Example 5

[0113] The X molecular sieve was prepared by referring to the method of Example 1, except that the heat treatment temperature of the ammonium exchanged molecular sieve X-2 was 500°C for 2.0 hours. The Ba mass content of the obtained X molecular sieve was 39.23% as BaO, and the K mass content was 0.62% as K2O.

[0114] The obtained X molecular sieve has a SiO2 / Al2O3 molar ratio of 2.43, a grain size of 1.0 μm, a total pore volume of 0.285 mL / g, a micropore volume of 0.246 mL / g, and a micropore specific surface area of ​​535.8 m 2 / g, and the mesopore specific surface area is 24.7m 2 / g, the mesopore volume is 0.039mL / g, the most probable pore sizes corresponding to the three mesopore distribution peaks on the pore size distribution curve are 6.0nm, 12.8nm and 19.8nm respectively, the mesopore volume ratio corresponding to the three mesopore distribution peaks is 64:8:1, and the relative content of the sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in its framework structure accounts for 68mol% of the total silicon species, and the relative content of non-framework aluminum accounts for 2.3mol% of the total aluminum species.

[0115] The molecular sieve performance test was carried out with reference to Example 1. The test results are shown in Tables 1 and 2.

[0116] Example 6

[0117] The X molecular sieve was prepared by referring to the method of Example 1, except that 0.18 mol / L barium chloride solution was used to carry out ion exchange on the heat-treated molecular sieve X-3. The Ba mass content of the obtained X molecular sieve was 40.38% as BaO, and the Na mass content was 0.26% as Na2O.

[0118] The SiO2 / Al2O3 molar ratio of the obtained X molecular sieve is 2.43, the grain size is 1.0 μm, the total pore volume measured by nitrogen physical adsorption is 0.321 mL / g, the micropore volume is 0.290 mL / g, and the micropore specific surface area is 629.8 m 2 / g, and the mesopore specific surface area is 25.7m 2 / g, the mesopore volume is 0.031mL / g, the most probable pore sizes corresponding to the three mesopore distribution peaks on the pore size distribution curve are 5.2nm, 14.2nm and 25.5nm respectively, the mesopore volume ratio corresponding to the three mesopore distribution peaks is 79:7:0.9, and the relative content of the sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in its framework structure accounts for 80mol% of the total silicon species, and the relative content of non-framework aluminum accounts for 0.6mol% of the total aluminum species.

[0119] The molecular sieve performance test was carried out with reference to Example 1. The test results are shown in Tables 1 and 2.

[0120] Comparative Example 1

[0121] Take 10.9 kg of sodium aluminate solution (containing 17.3% by mass of Al2O3 and 21.0% by mass of Na2O), 48.3 kg of deionized water and 13.1 kg of sodium hydroxide, stir to completely dissolve the solid alkali, then add 66.8 kg of water glass (containing 28.3% by mass of SiO2 and 8.8% by mass of Na2O), stir until uniform, and age at 25°C for 20.0 h to obtain a directing agent, wherein the molar ratio of each material is: SiO2 / Al2O3=17, Na2O / SiO2=0.95, H2O / SiO2=17.6.

[0122] Take 174 kg of water glass, 768 kg of deionized water, and 13 kg of sodium hydroxide, stir them thoroughly at 25 ° C, add 178 kg of sodium aluminate and mix them well, then add 0.8 kg of directing agent, stir evenly, and add 15 kg of dimethylhexadecyl [3-(trimethoxysilyl)propyl] ammonium chloride [(CH3O)3Si(CH2)3N(CH3)2(CH2) with a concentration of 60 mass % 15 CH3Cl] aqueous solution is used as the template (R) solution, and stirring is continued until the mixture is uniform to obtain a synthetic system, wherein the molar ratio of each material is: SiO2 / Al2O3=2.8, Na2O / SiO2=1.23, H2O / SiO2=65, the mass ratio of R / SiO2 is 0.06, and the amount of the directing agent added is calculated as 0.2% of the mass of SiO2 in the synthetic system based on the SiO2 therein.

[0123] The above synthesis system was heated to 100°C and hydrothermally crystallized for 8.0 hours under static conditions. The crystallized product was washed with deionized water until the pH value of the washing liquid was less than 10, and the obtained solid was dried at 80°C for 12.0 hours, calcined at 200°C in an air atmosphere for 1.0 hour, calcined at 380°C for 1.0 hour, calcined at 540°C for 4.0 hours, and dried at 90°C for 12.0 hours. The obtained product was then ion exchanged with a mixed solution of 0.18 mol / L barium chloride and 0.07 mol / L potassium chloride. The ion exchange was carried out in a column container at an exchange temperature of 90°C for 8.0 hours, and the liquid volume space velocity of the ion exchange was 6.0 h -1, then filtered and washed with 2000mL deionized water to obtain mesoporous X molecular sieve, the Ba mass content of the obtained mesoporous X molecular sieve is 37.52% as BaO, and the K mass content is 0.51% as K2O. Its SiO2 / Al2O3 molar ratio is 2.34, the grain size is 1.2μm, the micropore volume measured by nitrogen physical adsorption is 0.28mL / g, the mesopore volume is 0.16mL / g, and the pore size distribution curve is as follows Figure 8 The most probable pore size corresponding to the mesoporous distribution peak is 8.8 nm. The sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in its framework structure accounts for 55 mol% of the total silicon species, and the relative content of non-framework aluminum accounts for 5.6 mol% of the total aluminum species.

[0124] The molecular sieve performance test was carried out with reference to Example 1. The test results are shown in Tables 1 and 2.

[0125] Comparative Example 2

[0126] The X molecular sieve was prepared by referring to the method of Example 1, except that the first step of treating the barium salt solution was omitted. The Ba mass content of the obtained X molecular sieve was 39.57% calculated as BaO, and the K mass content was 0.59% calculated as K2O.

[0127] The SiO2 / Al2O3 molar ratio of the obtained X molecular sieve is 2.43, the grain size is 1.0 μm, the total pore volume measured by nitrogen physical adsorption is 0.369 mL / g, and the micropore specific surface area is 704.5 m 2 / g, and the mesopore specific surface area is 26.3m 2 / g, the mesopore volume is 0.035mL / g, and the pore size distribution curve is as follows Fig. 9 The most probable pore size corresponding to the mesoporous distribution peak is 4.2 nm. The sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in its framework structure accounts for 72 mol% of the total silicon species, and the relative content of non-framework aluminum accounts for 1.8 mol% of the total aluminum species.

[0128] The molecular sieve performance test was carried out with reference to Example 1. The test results are shown in Tables 1 and 2.

[0129] Comparative Example 3

[0130] The X molecular sieve was prepared by referring to the method of Example 1, except that the ammonium salt solution treatment step was omitted. The Ba mass content of the obtained X molecular sieve was 41.0% as BaO, and the K mass content was 0.65% as K2O.

[0131] The SiO2 / Al2O3 molar ratio of the obtained X molecular sieve is 2.43, the grain size is 1.0 μm, the total pore volume measured by nitrogen physical adsorption is 0.369 mL / g, and the micropore specific surface area is 571.8 m 2 / g, and the mesopore specific surface area is 2.1m 2 / g, the mesopore volume is 0.007mL / g, and the pore size distribution curve is as follows Fig.10 As described above, there is no mesoporous distribution peak. The relative content of the sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in its framework structure accounts for 88 mol% of the total silicon species, and the relative content of non-framework aluminum accounts for 0.5 mol% of the total aluminum species.

[0132] The molecular sieve performance test was carried out with reference to Example 1. The test results are shown in Tables 1 and 2.

[0133] Comparative Example 4

[0134] The X molecular sieve was prepared by referring to the method of Example 1, except that the heat treatment step was carried out at 600° C. for 2.0 h under a flowing air atmosphere. The Ba mass content of the obtained X molecular sieve was 27.70% as BaO, and the K mass content was 0.59% as K2O.

[0135] The SiO2 / Al2O3 molar ratio of the obtained X molecular sieve is 2.6, the grain size is 1.0 μm, the total pore volume measured by nitrogen physical adsorption is 0.292 mL / g, and the micropore specific surface area is 399.8 m 2 / g, and the mesopore specific surface area is 23.7m 2 / g, the mesopore volume is 0.138mL / g, and the most probable pore size corresponding to the mesopore distribution peak is 12.8nm. The sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in its framework structure accounts for 47mol% of the total silicon species, and the relative content of non-framework aluminum accounts for 9.3mol% of the total aluminum species.

[0136] The molecular sieve performance test was carried out with reference to Example 1. The test results are shown in Tables 1 and 2.

[0137] Table 1 Separation performance test results of molecular sieves obtained in various embodiments and comparative examples

[0138]

[0139] As shown in Table 1, the microporous-mesoporous X molecular sieve of the present application shows higher C8 aromatic hydrocarbon adsorption selectivity and shorter adsorption / desorption time compared with the X molecular sieve of the comparative example, indicating that the microporous-mesoporous X molecular sieve of the present application has higher C8 aromatic hydrocarbon separation and mass transfer performance.

[0140] Table 2 Test results of adsorption capacity and mass transfer performance of molecular sieves obtained in various embodiments and comparative examples

[0141] Example No. Toluene adsorption, mg / g Relative diffusion coefficient Example 1 181 1.42 Example 2 182 1.35 Example 3 179 1.47 Example 4 181 1.31 Example 5 178 1.85 Example 6 179 1.41 Comparative Example 1 162 1.05 Comparative Example 2 171 0.97 Comparative Example 3 175 1.01 Comparative Example 4 121 0.99

[0142] As shown in Table 2, the microporous-mesoporous X molecular sieve of the present application shows a higher toluene adsorption amount and relative diffusion coefficient compared with the X molecular sieve of the comparative example, indicating that the microporous-mesoporous X molecular sieve of the present application has a higher adsorption capacity and mass transfer performance.

[0143] The preferred embodiments of the present application are described in detail above; however, the present application is not limited to the specific details in the above embodiments. Within the technical concept of the present application, a variety of simple modifications can be made to the technical solution of the present application, and these simple modifications all fall within the protection scope of the present application.

[0144] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, this application will not further describe various possible combinations.

[0145] In addition, the various implementation modes of the present application may be arbitrarily combined, and as long as they do not violate the concept of the present application, they should also be regarded as the contents disclosed in the present application.

Claims

1. A microporous-mesoporous X molecular sieve, the micropore specific surface area of ​​which is 450-640 m2 as determined by nitrogen physical adsorption method 2 / g, preferably 500-640m 2 / g, more preferably 550-640m 2 / g, mesopore specific surface area is 20-50m 2 / g, preferably 20-30m 2 / g, and its pore size distribution curve shows at least two mesopore distribution peaks, wherein the most probable pore size corresponding to one mesopore distribution peak is in the range of 3.0-7.0nm, preferably in the range of 4.5-7.0nm, and the most probable pore size corresponding to the other mesopore distribution peak is in the range of 10.0-19.0nm, preferably in the range of 10.0-14.0nm, and the mesopore volume ratio corresponding to the two mesopore distribution peaks is preferably (100-20): (10-5) according to the pore size from small to large, and more preferably (80-60): (10-8); Preferably, the pore size distribution curve of the X molecular sieve shows at least three mesopore distribution peaks, wherein the most probable pore size corresponding to one mesopore distribution peak is in the range of 3.0-7.0 nm, preferably in the range of 4.5-7.0 nm, the most probable pore size corresponding to one mesopore distribution peak is in the range of 10.0-19.0 nm, preferably in the range of 10.0-14.0 nm, and the most probable pore size corresponding to another mesopore distribution peak is in the range of 19.0-30.0 nm, preferably in the range of 19.0-26.0 nm. More preferably, the mesopore volume ratios corresponding to the three mesopore distribution peaks are (100-20): (10-5): (1-0.1) from small to large pore size, preferably (80-60): (10-8): (1-0.5).

2. The X molecular sieve according to claim 1, wherein the SiO2 / Al2O3 molar ratio of the X molecular sieve is 2.0-2.6, preferably 2.2-2.

4.

3. The X molecular sieve according to claim 1 or 2, having a total pore volume of 0.24-0.35 cm 3 ·g -1 In the range of 0.26-0.35cm 3 ·g -1 The micropore volume is in the range of 0.22-0.33cm 3 ·g -1 In the range of 0.24-0.33cm 3 ·g -1 In the range, further preferably, the percentage of micropore volume of the X molecular sieve to the total pore volume is not less than 90.0%.

4. The X molecular sieve according to any one of claims 1 to 3, wherein the particle size of the X molecular sieve is 0.8-2.5 μm, preferably, the particle size of the X molecular sieve is 0.8-1.5 μm.

5. The X molecular sieve according to any one of claims 1 to 4, 29 Si and 27 According to the high-resolution magic angle nuclear magnetic resonance measurement of Al, the sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in its framework structure accounts for a relative content of not less than 60 mol%, preferably not less than 75 mol%, more preferably not less than 80 mol% of the total silicon species, and the relative content of non-framework aluminum accounts for not more than 3 mol%, preferably not more than 1.6 mol%, more preferably not more than 0.8 mol%.

6. The X molecular sieve according to any one of claims 1 to 5, wherein: At least part of the cation positions of the X molecular sieve are occupied by Ba and Na, and the Ba mass content of the X molecular sieve is in the range of 5.0-41.0% calculated as BaO, preferably in the range of 30-41.0%; the Na mass content of the X molecular sieve is in the range of 0.2-17.0% calculated as Na2O, preferably in the range of 0.2-2.0%; or At least part of the cation positions of the X molecular sieve are occupied by Ba and K. Calculated as BaO, the Ba mass content of the X molecular sieve is in the range of 30.0-41.0%, preferably in the range of 38.0-41.0%; calculated as K2O, the K mass content of the X molecular sieve is in the range of 0.2-3.0%, preferably in the range of 0.2-2.0%.

7. The method for preparing the microporous-mesoporous X molecular sieve according to any one of claims 1 to 6, comprising the following steps: 1) Partially ion exchange the NaX molecular sieve with a barium salt solution to obtain a Ba-modified molecular sieve; 2) performing partial ion exchange on the Ba-modified molecular sieve obtained in step 1) with an ammonium salt solution to obtain an ammonium-exchanged molecular sieve; and 3) placing the ammonium-exchanged molecular sieve obtained in step 2) under a flowing atmosphere at 100-500° C., preferably 120-300° C., for heat treatment for 0.5-6.0 h, preferably 2.0-6.0 h, and optionally, ion-exchanging the molecular sieve after heat treatment with a mixed solution of barium salt and potassium salt, or with a barium salt solution and a potassium salt solution respectively, to obtain a microporous-mesoporous X molecular sieve.

8. The method according to claim 7, wherein the NaX molecular sieve used in step 1) has one or more of the following characteristics: an octahedral morphology, a particle size of 0.8-2.5 μm, a SiO2 / Al2O3 molar ratio of 2.0-2.6, and / or, calculated as Na2O, a Na mass fraction of 15.0-17.0%.

9. The method according to claim 7 or 8, wherein the partial ion exchange in step 1) is carried out at 30-95° C., preferably 80-95° C., for 0.5-5.0 h, preferably 2.0-5.0 h; preferably, in step 1): The concentration of the barium salt solution is 0.05-1.0 mol / L; The barium salt is selected from barium chloride, barium nitrate, or a combination thereof; When the barium salt solution is subjected to ion exchange with the NaX molecular sieve, the volume space velocity of the barium salt solution is 2.0-10.0 h -1 , preferably 4.0-8.0h -1 .

10. The method according to any one of claims 7 to 9, wherein the partial ion exchange in step 2) is carried out at 25-95° C., preferably 50-75° C., for 0.2-5.0 h, preferably 0.2-2.0 h; preferably, in step 2): The concentration of the ammonium salt solution is 0.2-5.0 mol / L; The ammonium salt is selected from ammonium chloride, ammonium sulfate, ammonium nitrate, or a combination thereof; When the ammonium salt solution and the Ba-modified molecular sieve are subjected to ion exchange, the liquid-to-solid volume ratio of the ammonium salt solution to the molecular sieve is 0.1-10:1, preferably 1-5:

1.

11. The method according to any one of claims 7 to 10, wherein in step 3), the gas flow rate of the flowing atmosphere is 0.01-1.0 L / h / g molecular sieve, and the flowing atmosphere is a flowing air atmosphere or an inert flowing atmosphere, preferably a flowing air atmosphere.

12. The method according to any one of claims 7 to 11, wherein the ion exchange in step 3) is carried out at 30-95° C., preferably 80-95° C., for 2.0-48.0 h, preferably 8.0-24.0 h; preferably, in the ion exchange in step 3): The concentration of the barium salt is 0.05-1.0 mol / L; The concentration of the potassium salt is 0.01-0.2 mol / L The barium salt is selected from barium chloride, barium nitrate, or a combination thereof; The potassium salt is selected from potassium chloride, potassium carbonate, potassium sulfate, potassium nitrate, or a combination thereof; and / or The volume space velocity of the mixed solution of potassium salt and barium salt, the barium salt solution and the potassium salt solution when ion exchange is carried out with the heat-treated molecular sieve is 2.0-10.0h -1 , preferably 4.0-8.0h -1 .

13. Use of the microporous-mesoporous molecular sieve according to any one of claims 1 to 6 as an adsorbent, in particular as an adsorbent for the adsorptive separation of aromatic isomers.

14. A method for adsorptive separation of p-xylene from C8 mixed aromatics containing p-xylene by liquid phase adsorption separation, comprising the steps of contacting the C8 mixed aromatics with the microporous-mesoporous molecular sieve described in any one of claims 1 to 6 to adsorb p-xylene, and contacting the molecular sieve after adsorbing p-xylene with a desorbent to desorb the p-xylene.

15. The method according to claim 14, wherein the desorbent is selected from p-diethylbenzene, toluene, or a combination thereof.

16. The method according to claim 14 or 15, wherein the operating pressure of the adsorption separation is 0.3-1.5 MPa and the operating temperature is 120-190°C.

Citation Information

Cited By

  • X molecular sieve-based adsorbent, and preparation method therefor and use thereof

    WO2026061128A1